EFFECT OF STIRRING RATE ON ELECTROCHEMICAL CODEPOSITION OF Ni-SiC COMPOSITE - Hamal, Kailash; Rajbhandari, Armila; Gyawali, Gobinda; Lee, Soo Wohn (Scientific World, 2015)
Nickel-Silicon Carbide (Ni-SiC) composite has been prepared by electrochemical codeposition technique. Nickel sulfamate bath was used along with grain modifier saccharine and cationic surfactant cetyltrimetylammonium bromide (CTAB). The effect of stirring rate was systematically studied and optimized to get well dispersed SiC particles in appropriate amount. Mixed crystalline phase with reinforced [2 1 1] crystal orientation was obtained by XRD analysis. The result revealed that, 250 revolutions per minute (rpm) is optimum stirring rate for the electrochemical codeposition of Ni–SiC. Coating prepared at 250 rpm showed highest microhardness and lowest coefficient of friction with better surface morphology and well distributed nano SiC particles. Scientific World, Vol. 12, No. 12, September 2014, page 30-33